2011
DOI: 10.1016/j.clnu.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Reducing glucose infusion safely prevents hyperglycemia in post-surgical children

Abstract: The current recommended glucose infusion induces hyperglycemia in post-surgical children. A reduced glucose infusion safely reduced high glucose levels, while children were capable to sustain normoglycemia with increased endogenous glucose production. The reduced glucose infusion did not exacerbate the mild catabolic state in which the patients were.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…Furthermore, reduced glucose intake resulted in decreased blood glucose concentrations and not in hypoglycemia or increased protein catabolism. However, in contrast with our hypothesis and our previous study in healthy children undergoing elective craniofacial surgery, the glycemic target (4.0 to 6.0 mmol/L) was not achieved with reduced glucose intake [39]. In addition, it resulted in increased EGP due to increased glycogenolysis.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, reduced glucose intake resulted in decreased blood glucose concentrations and not in hypoglycemia or increased protein catabolism. However, in contrast with our hypothesis and our previous study in healthy children undergoing elective craniofacial surgery, the glycemic target (4.0 to 6.0 mmol/L) was not achieved with reduced glucose intake [39]. In addition, it resulted in increased EGP due to increased glycogenolysis.…”
Section: Discussioncontrasting
confidence: 92%
“…Under steady-state conditions, total glucose rate of appearance is equal to the rate of disappearance [37], the latter of which reflects glucose utilization. Rates of EGP, glucose clearance, glycogenolysis, and gluconeogenesis were calculated as previously described [21,39,40]. …”
Section: Methodsmentioning
confidence: 99%
“…While normal infants and children may have substantially higher glucose turnover rates than adults, 81 limited data from critically ill children suggest that glucose infusion rates (GIR) less than 5 mg/kg/min may be optimal for glucose utilization from PN. 82,83 Further, BG concentrations may not accurately reflect glucose turnover and utilization. 82 The practice of cycling PN may also be associated with development of SH, most likely due to impaired insulin secretion.…”
Section: Prolonged Immobility and Stress Hyperglycemiamentioning
confidence: 99%
“…It is therefore thought that parenteral nutrition creates a significantly higher blood glucose level which causes cellular glucose overload and oxidative injury in cells that do not require insulin for glucose uptake 7. Another small study recommended a reduction in glucose infusion as opposed to the aggressive use of insulin 15. Gandhi et al quantified the risk of intraoperative glucose and adverse events by formulating a continuous scale whereby every 20 mg/dL increase in blood glucose above 100 mg/dL was associated with a 34% increase in the likelihood of an adverse event 16…”
Section: Intensive Insulin Therapy In Adult Patientsmentioning
confidence: 99%
“…Interestingly, the survey showed that clinicians tend to undertreat due to a fear of inducing iatrogenic hypoglycemia. This was especially the case with the pediatric intensivists because of the unknown long-term effects of hypoglycemia 15,20. As documented in recently published correspondence, opinion still differs on what are considered “correct” blood glucose levels to aim for 20.…”
Section: Standards Of Carementioning
confidence: 99%